Analysis of various hole transport layers (HTLs) on the performance of CZTS- solar cell. (1st March 2023) - Dakua, Pratap Kumar; Panda, Deepak Kumar
Abstract: CZTS is a potential absorber material and received a lot of focus because of its excellent optoelectronic properties. To improve the functionality of CZTS-based solar cells, this study examines the potential HTLs (MoTe2, Cu2 O, and SnS) and their contribution to the better performance of the device. HTL improves the overall performance of the device by decreasing the recombination rate at the back contact and photon energy absorption. The impact of the various device parameters such as absorber layer thickness, defect densities, contact work functions, shunt and series resistances (RSh and Rs ), and the temperature of the device are briefly examined in this work. The research shows that Cu2 O and SnS are more emerged HTLs rather than MoTe2 . The device achieved a PCE of 24% and a FF of 74%. The results show that the addition of these HTLs significantly improved the Voc, Jsc, and FF, all of which are within the Shockley-Queasier limits. This study points to the possibility of producing more efficient CZTS heterojunction-based solar cells.